The Highland Towers disaster - Lara Ariffin; Harun Rahman; Hale, Chris; Novista Sdn. Bhd. (Kuala Lumpur: Novista Sdn. Bhd., 2010)
Why had Highland Towers collapsed, and who should be called to account? In this emotionally super charged real life story, we hear the raw heart rending stories of the men and women who lived through 12 days of torment - and expose in compelling detail the fatal flaws that led to the power of two hundred jumbo jets ramming into the foundations of Highland Towers.
Program shows on History Channel
Editors, Lara Ariffin, Harun Rahman ; executive producer, Chris Humprey
Narrator: Timothy Watson
dvd format
Keywords: Highland Towers (Ulu Kelang, Selangor); Building failures -- Malaysia -- Ulu Kelang (Selangor); Building failures -- Malaysia -- Ulu Kelang (Selangor) -- Investigations; Structural failures -- Investigations; Structural failures -- Malaysia -- Ulu Kelang (Selangor) -- Investigations; Disasters -- Malaysia -- Ulu Kelang (Selangor)